2016
DOI: 10.5935/0103-5053.20160194
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Pattern of Leaf, Flower and Fruit Specific Ambient Volatiles above an Oil Palm Plantation in Pará State, Brazil

Abstract: Oil palm plantations are rapidly expanding in the tropics because of insatiable global demand for fruit oil to be used in food, biofuels and cosmetics. Here we show that three tissue-specific volatiles can be quantified in ambient air above an African-American hybrid oil palm plantation in Brazil and linked photosynthesis (isoprene), floral scent (estragole), and for the first time, fruit oil processing (6-methyl-5-hepten-2-one, MHO). Plant enclosure techniques verified their tissue specific emission sources w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Some studies have shown that tree mortality and disturbance events are increasing in tropical forests (Brienen et al, 2015). Due to the effect of isoprene and monoterpenes on atmospheric chemistry at regional and global levels and to the protection of the photosynthetic apparatus, it is of great relevance to continue to investigate the presence of light-dependent leaf emissions of isoprene and monoterpene in tropical forests, especially given their high diversity and increased pressure from land use, expansion of deforestation, and changes in precipitation regimes (Chambers and Artaxo, 2017;Harrison et al, 2013;Jardine et al, 2016a;Khanna et al, 2017).…”
Section: Sharkey Andmentioning
confidence: 99%
“…Some studies have shown that tree mortality and disturbance events are increasing in tropical forests (Brienen et al, 2015). Due to the effect of isoprene and monoterpenes on atmospheric chemistry at regional and global levels and to the protection of the photosynthetic apparatus, it is of great relevance to continue to investigate the presence of light-dependent leaf emissions of isoprene and monoterpene in tropical forests, especially given their high diversity and increased pressure from land use, expansion of deforestation, and changes in precipitation regimes (Chambers and Artaxo, 2017;Harrison et al, 2013;Jardine et al, 2016a;Khanna et al, 2017).…”
Section: Sharkey Andmentioning
confidence: 99%
“…[23] A recent study reported that the African-American oil palm hybrid is a strong estragole emitter with some variations in the amount released throughout the day. [22] Due to the great amount of information promptly obtained in order to achieve a holistic view of the variability in the volatile compounds expelled according to the palm gender (male or female) and genotypes, a heat map evaluation was carefully performed. The heat map analysis presents the relative intensity of a value within a range, where the highest values (relative to the other present numbers) are given in 'hot' color (red), while those that are lower in their value are given 'cold' color (blue).…”
Section: Resultsmentioning
confidence: 99%
“…As far as the African oil palm, a recent study performed a correlative relationship between male and female inflorescences with the compound estragole. [22] Furthermore, other factors may also influence the pollination, such as wind, temperature, amount and effectiveness of the pollen, number of male and female inflorescences, the balance and interaction between the female and male flowers, as well as the use of the insecticides. [9,15,18] Therefore, the development of studies on metabolic profiling the emission of the VOCs by oil palm is important and it deserves a special attention regarding its importance to the reproduction success of the plant in its economic role and consequently increasing its production as well.…”
Section: Introductionmentioning
confidence: 99%
“…Deforestation has implied substantial environmental changes (Davidson et al., 2012) and forest disturbance (Bullock et al., 2020), such as water stress due to shallower roots (Huete et al., 2006) that causes an energy imbalance, loss of biodiversity, changes to carbon storage (Huete et al., 2006) and an overall decrease in BVOC emissions due to the loss of biomass (Scott et al., 2018). Biomass burning also profoundly affects the oxidation pathways of BVOCs and increases emissions of air pollutants (Bulbovas et al., 2014) by clearing land mainly for soy production (Bulbovas, de Souza, de Moraes, Luizão, & Artaxo, 2007), oil palm production (Jardine, Gimenez, et al, 2016) and cattle ranching (Figure 5). Soy crops are very sensitive to tropospheric ozone (Bulbovas et al., 2007), so higher ozone mixing ratios will feed back to more deforestation to counteract decreased soy productivity (Pimentel, 2011).…”
Section: Climate Change Land‐use Change and Feedbacksmentioning
confidence: 99%